Bioapplications of Bacterial Cellulose Polymers Conjugated with Resveratrol for Epithelial Defect Regeneration - En Meng (Polymers, 2019)
Excellent wound dressing is essential for effective wound repair and regeneration. However, natural polymeric skin substitutes often lack mechanical strength and hydrophilicity. One way to overcome this limitation is to use biodegradable polymers with high mechanical strength and low skin-irritation induction in wet environments. Bacterial cellulose (BC) is an attractive polymer for medical applications; unlike synthetic polymers, it is biodegradable and renewable and has a strong affinity for materials containing hydroxyl groups. Therefore, we conjugated it with resveratrol (RSV), which has a 4′-hydroxyl group and exhibits good biocompatibility and no cytotoxicity. We synthesized BC scaffolds with immobilized RSV and characterized the resulting BC/RSV scaffold with scanning electron microscopy and Fourier-transform infrared spectroscopy. We found that RSV was released from the BC in vitro after ~10 min, and immunofluorescence staining showed that BC was highly biocompatible and regenerated epithelia. Additionally, Masson’s trichrome staining showed that the scaffolds preserved the normal collagen-bundling pattern and induced re-epithelialization in defective rat epidermis. These results indicated that RSV-conjugated BC created a biocompatible environment for stem cell attachment and growth and promoted epithelial regeneration during wound healing.